Cervical Dystonia Is Associated With Aberrant Inhibitory Signaling Within the Thalamus - Groth, Christopher L.; Brown, Mark; Honce, Justin M.; Shelton, Erika; Sillau, Stefan H.; Berman, Brian D. (Frontiers in Neurology, 2021)
Objective: To investigate whether alterations in the neurotransmission of gamma-aminobutyric acid (GABA) in the thalamus are present in patients with cervical dystonia compared to healthy controls. Methods: GABA magnetic resonance spectroscopy was used to investigate concentration levels of GABA in the thalamus of cervical dystonia patients (n=17) compared to healthy controls (n=18). Additionally, a focused post-hoc analysis of thalamic GABAA receptor availability data in a similar cohort (n=15 for both groups) using data from a previously collected 11C-flumazenil positron emission tomography study was performed. Group comparisons for all evaluations were performed using two-sided t-tests with adjustments for age and sex, and Bonferroni correction for multiple comparisons was applied. Spearman’s coefficient was used to test correlations. Results: We found significantly reduced GABA+/Cre levels in the thalamus of cervical dystonia patients compared to controls, and these levels positively correlated with disease duration. Although mean thalamic GABAA receptor availability did not differ between patients and controls, GABAA availability negatively correlated with both disease duration and dystonia severity. Conclusions: These findings support that aberrant inhibitory signaling within the thalamus contributes to the pathophysiology of cervical dystonia. Additionally, these results suggest that an inadequate ability to compensate for the loss of GABA through upregulation of GABAA receptors may underlie more severe symptoms.